MEJA KERJA DENGAN ALAT PEMBUAT LUBANG PEN UNTUK MENINGKATKAN KUALITAS DAN KEqEPATAN ABSTRACT PEMBUATAN PINTU KAYU - -, Didik Nurhadiyanto; S, Suprapto Rachmad (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
In making wood crafting specially making of door and shutter leaf oftentimes obtained a handicapped door product at shares pen hole in the form of barst / break, the difficulty make the door leaf if market request quite a lot, and narrow tight workplace So that needed a workbench which muliti function so that all workable door making work the desk. Considering problems faced by this wood industry hence the industry require to be assisted by given a appliance of door maker in the lbnn of a workbench of multi function provided by the appliance of hole pen maker. With the workbench all worker can finish the work of door making start from cutting r.rf workpiece.making of hole pen come up with the setting. The aim of this program is to perform and make the workbench by means of hole pen to increase quality and time efficiency, so that small industry can do the more order. In executing this prograrn we take the following stages : (l) planning workbench to produce the leaf of door or window, matching with society condition. So that this appliance easy to accepted by society hence this appliance own the following specification : Easy to operate it, economizethe place, work of making of 'door leaf become easier, (2) testing workbench to make door in wood industry industry "UD.WARSIDI" to know until where the appliance performace, covering ist amenity and speed finish the making of door leaf. (3) door leaf yielded frorn this appliance compared to by its quality with the door leaf made conventionally. (4 ) machine completion its performance according to plan (5) delivering the machine at partner industry to be utilized so that can be productive. (6) compiling final report of activity execution. Result of inferential workbench perfomance test-drive as follows : (1) Maker of hole pen of this desk can function better. Hole diameter chisel between 9 up to l5 mm. (2) Compered to workmanship in conventionally making of hole pen with this desk is quicker till 4 times.(3) desk can be used bLtter to ieap the side goodness step aside and also wide side.(4) long desk of the size 2.03 m, wide o,g4 m, high 0,71m, speed turn around the motor is 2.800 rpm, speed turn around to drill 2.800 rpm, (5) with this workbench, during 2 day can make 8 shutter and 2 door leaf whereas without using workbench only can make 5 shutter and I door leaft (6) quality of result of work in making softer hote pen when compared to a manual work (?) efficiency of place use very high. 'Key *) word : workbench, hole pen, door, and window